A Non-canonical Melanin Biosynthesis Pathway Protects Aspergillus terreus Conidia from Environmental Stress. Issue 5 (19th May 2016) - Geib, Elena; Gressler, Markus; Viediernikova, Iuliia; Hillmann, Falk; Jacobsen, Ilse D.; Nietzsche, Sandor; Hertweck, Christian; Brock, Matthias
Summary: Melanins are ubiquitous pigments found in all kingdoms of life. Most organisms use them for protection from environmental stress, although some fungi employ melanins as virulence determinants. The human pathogenic fungus Aspergillus fumigatus and related Ascomycetes produce dihydroxynaphthalene- (DHN) melanin in their spores, the conidia, and use it to inhibit phagolysosome acidification. However, biosynthetic origin of melanin in a related fungus, Aspergillus terreus, has remained a mystery because A. terreus lacks genes for synthesis of DHN-melanin. Here we identify genes coding for an unusual NRPS-like enzyme (MelA) and a tyrosinase (TyrP) that A. terreus expressed under conidiation conditions. We demonstrate that MelA produces aspulvinone E, which is activated for polymerization by TyrP. Functional studies reveal that this new pigment, Asp-melanin, confers resistance against UV light and hampers phagocytosis by soil amoeba. Unexpectedly, Asp-melanin does not inhibit acidification of phagolysosomes, thus likely contributing specifically to survival of A. terreus conidia in acidic environments. Graphical Abstract: Highlights: Aspergillus terreus produces a novel type of melanin Pigment synthesis was reconstituted heterologously in vivo and in vitro An NRPS-like enzyme produces a substrate for tyrosinase-mediated polymerization The pigment protects conidia from biotic and abiotic stress factors Abstract : Geib et al. show that conidia of Aspergillus terreus produce an uncommon type of melanin by an NRPS-like enzyme. Aspulvinone E derives as precursor and is polymerized by the tyrosinase TyrP. The melanin specifically supports adaptation to the environment.